Chromatin fine structure profiles for a developmentally regulated gene: reorganization of the lysozyme locus before trans-activator binding and gene expression - Kontaraki, Joanna (Cold Spring Harbor Laboratory Press, 2000)
The chicken lysozyme locus is activated in a stepwise fashion during myeloid differentiation. We have used this locus as a model to study at high resolution changes in chromatin structure both in chicken cell lines representing various stages of macrophage differentiation and in primary cells from transgenic mice. In this study we have addressed the question of whether chromatin rearrangements can be detected in myeloid precursor cells at a stage well before overt transcription of the lysozyme gene begins. In addition to restriction enzyme accessibility assays and DMS footprinting, we have applied new, very sensitive techniques to assay for chromatin changes. Particularly informative was UV photofootprinting, using terminal transferase-dependent PCR and nonradioactive detection. We find that the basic chromatin structure in lysozyme nonexpressing hematopoietic precursor cells is highly similar to the pattern found in fully differentiated lysozyme-expressing cells. In addition, we find that only in nonexpressing cells are dimethylsulfate footprints and UV photofootprints affected by trichostatin, an inhibitor of histone deacetylation. These results are interpreted to mean that most chromatin pattern formation is complete before the binding of end-stage trans-activators, supporting the notion that heritable chromatin structure is central to the stable epigenetic programs that guide development.